Pengaruh Profitabilitas dan Kompleksitas Operasi Perusahaan Terhadap Audit Delay: Studi Pada Perusahaan Pertambangan Terdaftar di Bursa Efek Indonesia Peiode 2017-2021 - Pattinaja, Elna Marsye; Limba, Franco Benony; Wali, Lisna (Postgraduate, University of Mataram, 2024)
This research is used to determine the effect of profitability and complexity of company operations on audit delay with company size as a moderating variable. This study-based quantitative research on mining companies aims to determine whether these factors have an effect on audit delay. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX).The sample used was purposive sampling, there were 49 mining companies listed on the Indonesia Stock Exchange (IDX), the authors used 10 companies that match the sample criteria in this study. The analysis used in this study includes descriptive statistical analysis, classic assumption test, hypothesis testing using regression analysis of the difference in absolute value.The results of this study indicate that profitability has a negative effect on audit delay, the complexity of the company's operations has no effect on audit delay. Firm size is unable to moderate the relationship between profitability and audit delay and firm size is unable to moderate the complexity of the firm's operations on audit delay.